Derechos y humanos sobre la exclusión a través del derecho (2009)
Through this paper the author developed the idea that during the modern era, the law has been characterized by trying to cover up the whole human being existence, regulating it from born to death (I). In this context, the person is a key concept and it has been determinant for individuals to access the community benefits, organized in States, trough rights (II). In the last decades, several discussions have been sustained about inclusion and exclusion of individuals and groups, by increasing or reducing the access to rights (III). Thus, certain legal tools have been developed focused on exclusion, such as conditionality of rights, organized denegation of justice and creation of under-statutes and identities (IV).